Magan : the land of copper : prehistoric metallurgy of Oman - Giardino, Claudio, 1952- (Archaeological heritage of Oman, 2019)
This volume describes the geography and environments of Oman, its rich copper ore deposits and the ancient mining and smelting techniques, and it also includes an overview of the physical properties of the different metals exploited in antiquity and of the analytical techniques used in archaeometallurgy.